2018
DOI: 10.1186/s11671-018-2451-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nanoscale Friction Behaviors of Graphene on Gold Substrates Using Molecular Dynamics

Abstract: In this paper, we investigate the friction behaviors of graphene flakes sliding on a gold substrate using molecular dynamics simulations. The effects of flake size, flake shape, relative rotation angle between flake and substrate, and crystal orientation of substrate on the friction process are thoroughly studied. It is found that under the same load, the average friction forces per atom are smaller for a bigger graphene flake, which exhibits an obvious size effect. It is also shown that flake shape is critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
(58 reference statements)
2
9
0
Order By: Relevance
“…Friction forces were plotted with respect to the sliding distances over the diamond surface in Figure 9 for the simulation at 0 K for different chiralities. According Figure 9, the interfacial friction force between graphene and the diamond substrate exhibited stick-slip motion behavior [27] and had a periodicity of 3.6 Å. The periodicity in the frictional force is considered to be due to the periodic lattice arrangement in both graphene and diamond, and it is in agreement with the behavior of the friction force of graphene nanoflakes on Au substrate [27].…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Friction forces were plotted with respect to the sliding distances over the diamond surface in Figure 9 for the simulation at 0 K for different chiralities. According Figure 9, the interfacial friction force between graphene and the diamond substrate exhibited stick-slip motion behavior [27] and had a periodicity of 3.6 Å. The periodicity in the frictional force is considered to be due to the periodic lattice arrangement in both graphene and diamond, and it is in agreement with the behavior of the friction force of graphene nanoflakes on Au substrate [27].…”
Section: Resultsmentioning
confidence: 82%
“…It is observed that at 0 K, the friction coefficient varied from 0.0044 to 0.0208 for different chiralities, where the interfacial friction coefficient is the lowest along the armchair sliding direction and the highest along the zigzag direction. The interfacial friction coefficients of the graphene–diamond interface are generally lower than those of the graphene–gold interface [27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because IBS is conducted in a near-vacuum environment, the influence of the environment can be ignored. As shown in Figure 1 , the aluminum sample is divided into three regions: the region of boundary atoms to fix the sample in space, the region of thermostat atoms to imitate the heat dissipation, and the region of Newtonian atoms which obeys Newton’s second law [ 30 , 31 , 32 , 33 ]. The thickness of thermostat layer and boundary layer are both 1 nm.…”
Section: Simulation Methodsmentioning
confidence: 99%